The relationship between primary tumour thicknesses in cancers of the oral cavity to subsequent lymph node metastasis - Fawzy, Ahmed; Al zaqri, Waleed Ali; Sabry, Mohamed; Sabry, Ahmed; Fol, Hosam El; Kased, Ahmed El (International Surgery Journal, 2017)
Background: Elective dissection of cervical lymph nodes in oral cavity cancers gives very precious data on its pathological state, judge for adjuvant therapy requirement plus its therapeutic effect but it has its morbidities that cannot be condoned. Tumor thickness (TT) in oral cavity cancers show an increasing value to be one of the most important and reliable factors that have a great relationship to regional node involvement. Methods: Forty-three patients with T1, T2 oral cavity squamous cell carcinoma with clinically and radiologically negative cervical L.Ns underwent elective neck dissection and the relation between the tumor thickness and the nodal metastasis was monitored. Tumor thickness was estimated preoperatively by using the intra-oral ultrasound and confirmed by histopathology postoperatively. Results: Only 12 out of 43 neck dissections (27.9%) showed positive L.Ns metastasis of primary tumor. The excised number of L.Ns ranged from 15 to 31 with mean±SD (21.58±3.59) L.Ns. The (TT) ranged from 1.4 mm to 7.8 mm. Our statistical results showed that there is a cutoff point which was 4 mm where (TT) > 4 mm showed significant results with histologically found positive cervical node metastasis compared to (TT) ≤4 mm specimens. Conclusions: Relationship of tumor thickness to lymph node metastasis was found to be significant as shown by this study. Our results clearly demonstrate that conservative elective neck dissection is indicated in patients with stage I/II oral cavity carcinoma whose tumors are > 4 mm in thickness as they mostly have latent metastasis.